IMPLEMENTASI KEBIJAKAN MANAJEMEN KEUANGAN PADA BADAN PENGELOLAAN KEUANGAN DAN ASET DAERAH KABUPATEN MAMUJU UTARA - Patu, Luthfi (Katalogis, 2016)
Objective to know the form of an evaluation of the aspects of the barriers of government policy on financial supervision in Finance and Asset Management Agency District of North Mamuju. This type of research is qualitative. The method used is the collection of the data include: interviews, direct observation, and Documentation. Based on the results of the research implementation implemntasi Policy manajmen Finance Agency Financial Management and Asset District North Mamuju still need mandapat subsidy centers, because of the budget than income became a benchmark of the failure of the implementation of regional autonomy because of the data known that the region still require subsidies from and the center has not been able to manage existing resources seen from policy changes related to the welfare of society, it should be analyzed the characteristics of the problem. The amount of local expenditure than revenue due to the region in the process of financial management override of political communication between local government and parliament that is representative of the totality of the percentage of the population covered by the target group. So the program to achieve policy goals are not.